Pengaruh Utang Luar Negeri, Kebijakan Fiskal Terhadap Konsumsi Masyarakat dalam Paradigma Ricardian Equivalence 1990-2004: Penerapan Model Vector Autoregressions (VAR) - Lukman Hakim (Economic Journal of Emerging Markets, 2006)
This study to apply Ricardian Equivalence concept in problem of debt in Indonesia. Ricardian Equivalence express that intrinsically governmental debt represent burden to society. Equally, governmental debt in this time is burden expenditure of society in the next year. But with assumption that society behave rationally, hence the debt burden will not in¬fluence society consumption.Based on Kormendi model (1983, 1990, 1995), this study analyse influence inde¬pendent variable to dependent variable. Independent variable are national income (GDP), governmental expenditure (G), tax (TX), subsidy (TR), governmental debt instalment (GINT), and total government debt  (GB), and dependent variable is society consumption (PC). This Study used Vector Autoregression (VAR) method which consist of decomposition variance and impulse response analysis. Decomposition variance analysis seen that before crisis period, consumption is in¬fluenced strongly by fiscal policy, consumption and national income. Meanwhile, ini period crisis a period, consumption is influenced by fiscal policy, government debt and government debt instalment. Impulse response analysis found that fiscal policy have effected strongly to consumption in before and after crisis period. On the contrary, tax had an effect weakly to consumption, although do not negativity Meanwhile at before and a period of economic cri¬sis, governmental debt and debt instalment had an effect strongly to consumption. Besides, before crisis national income have influence stronger than subsidy to consumption. But a crisis period, subsidy influence exactly to consumption than to national income.Pursuant to that finding can be expressed that researching into is in general sup¬port of Ricardian Equivalence perspective according to empirical finding of Kormendi, dif¬ferent only fiscal policy influence to consumption. Theoritical of RE state fiscal policy do not have an effect on to society consumption, but in this research exactly have strong influence. One of argument is since New Order till governance these days, fiscal policy still so central as a means of stimulus growth of national economy. Keywords: government debt, ricardian equivalence, var and impulse respond analysis.